2015
DOI: 10.1016/j.hlc.2015.06.763
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Aboriginal patients’ experiences of cardiac care at a major metropolitan hospital in Melbourne

Abstract: Conclusions: Despite higher rates of baseline comorbidities and presentation with MI, Indigenous Australians do not have worse in-patient outcomes following PCI. Given the higher rates of baseline co-morbidities, it will be essential to determine long-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…The age of participants ranged from 24 to 89 years old. The included studies were conducted in 6 different countries: 15 in the United States [ 8 , 26 – 39 ], 3 in the United Kingdom [ 40 42 ], 2 in Australia [ 43 , 44 ], 1 in Canada [ 45 ], Spain [ 46 ] and Hong Kong [ 47 ] respectively. 11 studies reported findings from the African American community, 2 each from the Pakistani, Indigenous Australian and South Asian communities and 1 each from the African Caribbean, Latin American, Native American, Roma and Iranian communities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The age of participants ranged from 24 to 89 years old. The included studies were conducted in 6 different countries: 15 in the United States [ 8 , 26 – 39 ], 3 in the United Kingdom [ 40 42 ], 2 in Australia [ 43 , 44 ], 1 in Canada [ 45 ], Spain [ 46 ] and Hong Kong [ 47 ] respectively. 11 studies reported findings from the African American community, 2 each from the Pakistani, Indigenous Australian and South Asian communities and 1 each from the African Caribbean, Latin American, Native American, Roma and Iranian communities.…”
Section: Resultsmentioning
confidence: 99%
“…Minority patients reported that healthcare providers ignored or rushed them during their clinical interactions [ 32 , 40 , 41 , 44 , 47 ]. Some patients further stated that they received less priority and were unfairly skipped over by patients of perceived privileged races [ 29 , 31 , 32 , 34 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the factors contributing to Indigenous health disparity lies in how Indigenous peoples experience hospitalisation in terms of their perception, expectation and interpretation of their healthcare encounters (Chapman, Smith, & Martin, ; Shahid, Finn, Bessarab, & Thompson, ; Worrall‐Carter et al., ). These studies demonstrate that they are faced with common challenges when encountering health care, such as language barriers, the need to relocate to access services and cultural isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Our results contribute to what is continuously cited as a barrier to highquality care for Aboriginal Australians when in hospital. [20][21][22] Poor communication from staff, financial stressors and disrespect for Aboriginal cultural norms are barriers to Aboriginal families accessing necessary health services, thereby impacting on their overall health outcomes. Our findings suggest that while healthcare providers deliver evidencebased care, they also need to communicate respectfully with Aboriginal Australians to strengthen relationships and create a more inclusive environment that contributes to Aboriginal patients feeling culturally safe.…”
Section: Discussionmentioning
confidence: 99%